The Functioning of the Iterative in Anton Chekhov’ Stories - Semenova, Nina (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The article presents the hypothesis that in Chekhov’s late stories the increasing share of iterative storytelling is a consequence of the reduction of eventfulness. The relations between the singular and the iterative in the story “The Two Volodyas” are presented. Lexical markers of the iterative are considered, which makes it possible to reconstruct the event in the logic of movement from the deep, verbal, level to the “surface” structures.